ANALISIS JALUR DISTRIBUSI INDUSTRI GULA DENGAN MENGGUNAKAN METODE INPUT OUTPUT - I.D., Riski Nur (Fakultas Ekonomi, UIN Maliki Malang, 2013)
The model of sugar industry distribution channel consist of sugarcane farmers, suppliers, millersand distributors. In this research, we analyze the distribution channel of sugar industry model by using inputoutput method. The analysis is used to know Backward Linkages and Forward Linkages of intersector. Thelinkages can identify key sector that have a big influence on the development of other sectors. The result ofmodel analysis show that there is no sector that has high Backward and Forward Linkages, so there is no keysector in sugar industry distribution channel.